Archaeological recontextualization and first direct 14C dating of a "pseudo-excise" decorated antler point from France (Pégourié Cave, Lot). Implications on the cultural geography of southwestern Europe during the Last Glacial Maximum. (February 2019) - Ducasse, Sylvain; Pétillon, Jean-Marc; Chauvière, François-Xavier; Renard, Caroline; Lacrampe-Cuyaubère, François; Muth, Xavier
Abstract: During the Last Glacial Maximum (LGM), very specific but rare osseous decorated artifacts were produced using the "pseudo-excise" technique. These artifacts present a large geographical distribution, extending at least from the Aquitaine basin to Asturias. While in France a Badegoulian age is traditionally accepted for the "pseudo-excise" technique, this is mostly based on arguable data from old excavations and/or problematic archaeostratigraphic contexts. Since it is a key-site for this matter we have focused our attention on Pégourié Cave (Lot, France) in order to establish the chronocultural attribution of pseudo-excised pieces in southwest France. The interdisciplinary reassessment of the lithic and osseous industries from Layer 8 and 9, including inter-layer refittings, has shown (1) the irrelevance of previous stratigraphic subdivisions and (2) the strong cultural heterogeneity of this assemblage, which combines Azilian, Magdalenian, Badegoulian, Solutrean and Gravettian components. At the same time, a broad 14 C program based on the direct dating of specific bone and antler technical wastes and tools—including a pseudo-excised point—was implemented after 3D recording using photogrammetry. The results obtained have allowed us to establish a new, firm confirmation of the Badegoulian age of pseudo-excised decoration and, in doing so, to more precisely define the time-range of this specific feature's trans-regional dissemination. Finally, by comparing the results with recent data notably obtained at Llonín cave (Asturias, Spain), new light has been shed on the cultural geography of southwestern Europe during the LGM, allowing us to discuss and fuel the still-controversial "Iberian Badegoulian" hypothesis. Graphical abstract: Unlabelled Image Highlights: Direct 14 C dating confirms the Badegoulian age of the "pseudo-excise" technique The defined chronological-range is comparable to data recently obtained in Asturias for "pseudo-excise"-yielding industries These results fuel the long-lasting debate around the existence of Badegoulian-like traditions in Spain An archaeostratigraphic reassessment shows that Pégourié can no longer be considered a reliable stratigraphy for the Badegoulian We also present a specific and little-destructive sampling protocol together with prior photogrammetric recording of each piece